Articular manifestations in patients with inflammatory bowel diseases treated with anti-TNF. Issue 1 (28th January 2022) - Cachen, Laurie; Nocturne, Gaetane; Collins, Michael; Meyer, Antoine; Gleizes, Aude; Hacein-Bey-Abina, Salima; Carbonnel, Franck; Mariette, Xavier; Seror, Raphaele
Abstract : Objective: To describe and identify factors associated with articular manifestations occurring in patients treated with anti-tumour necrosis factor (TNF) for inflammatory bowel diseases (IBDs). Methods: Retrospective monocentric study, including all patients who received an anti-TNF for an IBD in our hospital. All incident articular manifestations occurring during treatment were analysed. Characteristics of patients with paradoxical articular manifestations were compared with that of patients without inflammatory articular manifestations. Results: Between February 2013 and May 2017, we identified 442 patients (36.2±15 years, 50.5% men) who had ever received an anti-TNF for an IBD: Crohn's disease (n=277), ulcerative colitis (n=154) and undetermined colitis (n=11). 115 (26%) patients developed new articular manifestations after a mean of 20 (±22) months of treatment. Among them, 59 (13.3%) had inflammatory manifestations: paradoxical in 39%, concomitant of an IBD flare in 27%, linked to an immunisation against anti-TNF in 27% and 7% to another diagnosis. Among paradoxical articular manifestations, 19 (83%) were new articular symptoms, including 8 (35%) de novo spondyloarthritis. There were no predictive factors of paradoxical articular manifestation. Paradoxical manifestations spontaneously resolved in 16 (70%) patients despite continuation of anti-TNF. Conclusion: Inflammatory articular manifestations occurred in about 13% of patients treated with anti-TNF for IBD. More than a quarter were linked to an immunisation against anti-TNF, which has to be searched in this situation. About 40% were paradoxical. In most of cases, they were transitory and did not require anti-TNFs discontinuation.